Public views and experiences on challenges related to drug treatment focusing on adverse drug reactions : A cross-sectional survey - Halonen, Nelli (My University, 2025)
Various factors affect the success of drug treatment, such as drug-drug-interactions and adverse drug reactions. We studied the experiences and perceptions of the general Finnish public on their drug treatment. This project was conducted as a cross-sectional survey using an electronic survey tool Webropol. The survey was distributed in late March 2024 to adult-age pharmacy customers consented to receive electronic newsletters and survey invitations. Link to the survey was also shared via social media. The data was analysed mainly by using descriptive statistics, and one-way ANOVA or t-test were used to study the associations of demographic factors with perceptions and experiences. We received 6927 full responses. The majority (87%) of the respondents reported having at least one chronic disease and 38% were polypharmacy patients using five or more drugs. During the last three months, 29% reported having experienced adverse drug reactions related to prescription drugs or hospital drugs and 5% related to over-the-counter drugs. Of all respondents, 10% reported that adverse drug reactions disrupt their daily life, and 23% were concerned about drug-drug interactions. About 80% of the respondents felt they received enough reliable medication counselling regarding their drug treatment and 79% were satisfied with the effectiveness of their drug treatment. Reported experienced adverse drug reactions were associated with more concerns and dissatisfaction with drug treatment. Overall, the respondents were concerned about adverse drug reactions, which they also had frequently experienced. However, most of the respondents were satisfied with the effectiveness of their drug treatment, and felt they can influence it themselves.
Keywords: adverse drug reactions, drug-drug interactions, medication-related burden, medication counselling, chronic diseases